(untitled) (International Journal of Innovative Technologies in Economy, 2019)
The article deals with issues related to the export-import of goods between Ukraine and the EU countries (in general), namely: the general structure of export and import by specific groups of goods, which occupy the largest share in the total volume of export-import goods. The analysis of the main indicators has been carried out: changes in the commodity structure in the reported year compared to the previous period, as well as disrupted problems of the entry of Ukraine into the EU market as a full-fledged exporter. The dependence between efficient use of resources and production of export- oriented products, as well as between the correct interpretation of the regulatory framework and the rational foreign policy of the state, has been proved.